ANALISIS PENGARUH MODAL USAHA, LAMA USAHA, TENAGA KERJA DAN LOKASI USAHA TERHADAP PENDAPATAN USAHA FOTOCOPY DI WILAYAH GOMONG KOTA MATARAM - Lalu M. Imam Hidayat; Ahmad Suhendri (Jurnal Kompetitif : Media Informasi Ekonomi Pembangunan, Manajemen dan Akuntansi, 2022)
The purposes of this study are 1) To find out whether Business Capital, Length of Business, Labor and Business Location have a significant effect on Partial Photocopying business income in Gomong, Mataram City. 2) To find out whether Business Capital, Business Length, Manpower and Business Location have a significant effect on Photocopying business income significantly in Gomong, Mataram City. 3) To find out what factors are the most dominant in influencing photocopying business income in Gomong, Mataram City. The research method used is associative with a quantitative approach. This research was conducted in the Gomong area of Mataram City. The sample in this study was 20 samples. The data collection technique used in this research is to use a questionnaire. The data analysis tool uses multiple linear regression analysis, T test, F test, and the coefficient of determination test (R2). The results of this study indicate that: 1) Business capital has a partial effect on photocopying business income in Gomong, 2) Business length has a partial effect on photocopying business income in Gomong. 3) Labor has a partial effect on the photocopying business income in Gomong. 4) The location of the business has a partial effect on the photocopying business income in Gomong. 5) Simultaneously, the four variables, namely business capital, length of business, labor and business location, have an effect on operating income.